THE EFFECT OF HEALTH EDUCATION ON KNOWLEDGE ABOUT ADOLESCENT REPRODUCTIVE HEALTH IN SMK TAMAN SISWA OF NANGGULAN KULON PROGO - Lutfiyati, Afi (Jurnal Kesehatan Samodra Ilmu (JKSI), 2023)
Background: The results of the 2017 Indonesian Demographic and Health Survey (SDKI) on Adolescent Reproductive Health (KRR) stated that adolescent knowledge about reproductive health was inadequate due to a lack of information which led adolescents toward risky behavior, such as having sex freely, which causes the emergence of diseases related to reproduction including Sexually Transmitted Infections (STI), Human Immunodeficiency Virus (HIV) or Acquired Immune Deficiency Syndrome (AIDS). The effort to increase adolescent knowledge is made through adolescent reproductive health counseling with video media. The objective of the Research: To investigate the effect of health education on knowledge about adolescent reproductive health at SMK Taman Siswa Nanggulan. Method: This study used a pre-experimental design with one group pretest-posttest design. The population of this study were all students of class XI at SMK Taman Siswa Nanggulan Kulon Progo with the total of 84 people. The sampling technique using purposive sampling obtained 51 samples. Health education interventions on reproductive health use audiovisual, namely video counseling. Data were collected using a reproductive health knowledge questionnaire. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The knowledge possessed by respondents before being given health counseling showed that most of them had low knowledge (52.9%), while after being given health counseling, they showed moderate knowledge (58.8%). The results of the Wilcoxon Signed-Rank Test obtained a p-value = 0.001 (p <0.05). Conclusion: There is an effect of health education on knowledge about adolescent reproductive health at SMK Taman Siswa Nanggulan.